X-Ray Diffraction Contrast Tomography for Probing Hydrogen Embrittlement in Heat-Treated Lean Duplex Stainless Steel - Eguchi, Kenichiro; Burnett, Timothy L.; Engelberg, Dirk L. (Frontiers in Materials, 2022)
Graphical Abstract